The Effect of Ethanol Polarities on Tannin Content of Persea americana Mill Seeds Extract Using Gelatin Precipitation Method - Sri Wardatun; Siti Mahyuni; Jeni Sri Mulyani (Study Program of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Pakuan, 2024)
Persea americana Mill (avocado) seed waste contains tannin compounds with several benefits and high economic value. Tannin is a natural compound widely used in various industries, including the pharmaceutical industry. The difference in concentration of ethanol causes polarity differences. This research aims to determine the effectiveness of tannin extraction from avocado seed using different concentration polarities of ethanol as a solvent. The dry powder of avocado seed was macerated in ethanol at concentrations of 30, 50, 70, and 96% for 72 hours, respectively. The gelatin precipitation method was applied to determine the tannin content in each extract; absorbance was read using a spectrophotometer UV-Vis, and the Folin Ciocalteu reagent was added to the avocado seed extract before spectrophotometer measurement. The results show that the polarity of ethanol has a significant effect (p<0.05) on the yield extract and tannin level in each extract. The extract yield and tannin content in avocado seed extracted with 30, 50,70 and 96% ethanol were 21.47%, 26.70%, 30.40%, and 47.67%, while the tannin content was 32.27 mg/g, 50.58 mg/g, 60.94 mg/g, and 85.30 mg/g respectively. The highest extract yield and tannin content are found in avocado seed extracted with 96% ethanol, which has lower polarity. It can be concluded that 96% ethanol is the best solvent to extract tannin from avocado seeds.